Construction of Contemporary Fiqh in the Disorders of Sexual Development Problems Through the Integration of Maqâshid al-Sharî’a and Medical Science - Ja'far, A. Kumedi; Susilo, Edi; Mursyid Al Haq (al-'adalah, 2025)
The discussion of Islamic jurisprudence on the position of people with Disorders of Sexual Development (DSD) is still uncertain and unfinished; there is even an impression of discrimination. This tendency can be seen in several worship procedures. For example, in the implementation of congregational prayer, people with DSD are not allowed to join with women or with men. They must be between groups of men and women. On the other hand, medical involvement is still not covered by Islamic jurisprudence, even though the medical review of DSD is not as simple as in Islamic jurisprudence. Therefore, efforts to formulate contemporary Islamic jurisprudence that provides solutions to various DSD problems are a necessity. This study employs a qualitative approach, utilizing the maqâshid al-sharî’a framework, which is complemented by a medical review. This study concludes that congenital reproductive disorders since birth in a person with DSD must be treated quickly and accurately by looking at the structure/characteristics of chromosomes, internal and external genitalia, and several other medical aspects to ensure gender identity through a medical approach. This is in line with the objectives of Islamic Sharia, namely to protect religion, protect descendants, and realize the welfare of the community.